Analisis Vegetasi Pada Berbagai Kondisi Mataair di Bagian Utara dan Tengah Kabupaten Gunungkidul Provinsi Daerah Istimewa Yogyakarta - , ATRIN RANGKISANI, Dr. Langgeng Wahyu Santosa, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Spring as one of the groundwater resource is the mainsource of the community in meeting the needs of water, which apparently happens in a number of springs in Gunungkidul, Yogyakarta. Hydrological functions of vegetation in making up an ecosystem is one of the most important environmental functions as watersheds through an interception process. To ensure the quality and quantity of water sufficiency, such appropriate efforts must be made, for example with the study of vegetation analysis on water resources. The purpose of this research are: to study biodiversity, structure and composition of vegetation in various springs conditions in northern (Baturagung Hills) and central (Wonosari Basin) Gunungkidul